2012
DOI: 10.2478/s11535-012-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Dependence between Cu concentration in the liver, kidneys and skeletal muscles of canine females

Abstract: Abstract:The aim of the investigations was the determination of the Cu contents in the liver, kidneys and skeletal muscles of canine females.Material for research was collected post mortem from 45 animals aged 1 to 18 years coming from the Warsaw area. The effect of the health state, age and life conditions on the distribution of copper in the investigated organs was estimated. That element was determined using the method of inductively coupled plasma-atomic emission spectrometry (ICP-AES). In the liver, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Most often, they manifested themselves as neurological disorders in a form of enzootic ataxia [ 14 16 ]. Described symptoms result from the fact that Cu is an element determining proper course of metabolic processes, like e.g., cell respiration, activity of nervous system (copper participates in the formation of neurotransmitters), building of connective tissues, and production of pigments in tissues [ 7 , 17 , 18 ]. Biological role of Cu is a result of its properties as a component or activator of enzymes such as peroxide dismutase, ceruloplasmine, cytochrome oxidase, tyrosinase, dopamine hydroxylase, and lysine oxidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most often, they manifested themselves as neurological disorders in a form of enzootic ataxia [ 14 16 ]. Described symptoms result from the fact that Cu is an element determining proper course of metabolic processes, like e.g., cell respiration, activity of nervous system (copper participates in the formation of neurotransmitters), building of connective tissues, and production of pigments in tissues [ 7 , 17 , 18 ]. Biological role of Cu is a result of its properties as a component or activator of enzymes such as peroxide dismutase, ceruloplasmine, cytochrome oxidase, tyrosinase, dopamine hydroxylase, and lysine oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Copper concentration in adult mammals is from 1.5 to 2.5 mg∙kg −1 body mass [ 19 , 20 ]. Due to specific anatomical features of digestive system in ruminants, there is an interaction between copper and antagonists, particularly molybdenum and sulfur, which in the rumen results in the production of thiomolybdates [ 18 ]. An important issue is the demand of rumen microflora for Cu which is lower than the demand of host’s tissues and amounts 1.57 μmol∙kg −1 of dry mass of fodder.…”
Section: Discussionmentioning
confidence: 99%
“…Due to being widespread, rubidium may substitute potassium in metabolic reactions, which may disturb their proper course. Even though the importance of rubidium for animals is not clearly understood, studies performed so far have indicated that Rb may be an essential element but the margin between its necessary and toxic level is very narrow (Angelow 1994 ; Kośla et al 2002 ; Milman et al 2006 ; Skibniewska et al 2012b , 2013b ). The mean content of rubidium in muscles of analysed red deer was lower than that reported by Jarzyńska and Falandysz ( 2011a ).…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors affecting the absorption of Mn, Cu and Zn, which may be both activators and inhibitors of that process. What is more, most elements demonstrate synergistic or antagonistic action towards each other [Kośla et al 2004;Skibniewska et al 2012]. It is suggested that the effect of kiwi fruits on the bioavailability of Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Cu, the liver is a better source for estimating the bioavailability of this trace element and these results will be published soon [Leontowicz et al in press]. Zinc, copper and manganese are among the elements that are considered to be essential, as their presence conditions a proper course of metabolic processes and their deficit or excess leads to serious disturbances of the health state [Kośla et al 2004;Skibniewski et al 2010, Skibniewska et al 2012]. …”
Section: Streszczeniementioning
confidence: 99%